An experimental and simulation screening of X-65 steel weldment corrosion in high flow rate conditions - Nofrizal, Nofrizal; Wulandari, Meyliana; Impey, Susan A.; Georgarakis, Konstantinos; Papanikolaou, Michail; Raja, Pandian Bothi (Elsevier, 2024)
Over many decades, the oil and gas industry has encountered significant challenges due to weldment corrosion. The issue of internal-pipeline local corrosion at the welded joint region has garnered significant concern, especially due to the combined impact of high shear stress and electrochemical corrosion. This combination can lead to pipeline rupture with relative ease. Hence, a new approach to screen the flow corrosion of X-65 steel via electrochemical methods, predicting fluid shear stress and velocity using computational fluid dynamic (CFD) simulation is positively tested and presented here. For that, the X-65 steel specimens were cut/designed as the inner, centre, and outer electrodes of the target to analyse the Weld Metal (WM), Heat Affected Zone (HAZ), and Parent Metal (PM). Electrochemical screening was carried out simultaneously at a flow of 10 m/s using a brine solution saturated with CO2. The PM and HAZ will corrode less than the WM, in some cases at 30–23% of the rate of the WM. Thus in an environment of uninhibited brine saturated with CO2 at 10 m/s, preferential weld corrosion (PWC) is expected to occur. In addition, the surface morphology screening (scanning electron microscope with energy dispersive x-ray analysis, X-Ray diffraction, focus ion beam, raman spectroscopy) was employed to monitor the corrosion damage on the metal surface and also to support the electrochemical measurements (linear polarization resistance, galvanic measurement, and electrochemical impedance spectroscopy).
Keywords: Computational fluid dynamics; Electrochemical; Heat affected zone; Parent metal; Weld metal